TWENTY YEARS OF LAW 10.639: HOW IS THIS LAW EFFECTIVE IN A COLLECTION OF MATHEMATICS TEXTBOOKS? - de Souza Cruz, Lucas Gabriel [UNESP]; Ince, Jamaal Adetoro [UNESP] (Universidade Federal de Sao Paulo, 2023)
This text presents an analysis of a collection of Mathematics textbooks, carried out for the discipline “Analysis of Mathematics Books and Teaching Materials”, taught in the Graduate Program in Mathematics Education at the Universidade Estadual Paulista “Júlio de Mesquita Filho”. Inspired by the methodology of vertical and horizontal analysis of textbooks, this work aims to understand in what ways the law 10.639/2003 is effective in textbooks that satisfy the demands of the New High School and the BNCC – Base Nacional Comum Curricular. Presenting the historical movements of black populations, mainly the Brazilian one, the text is inspired by the two decades of that law to conduct the analysis criteria and seek to understand in what ways the analyzed collection acts in the constitution of the mathematical identity of black students. At the end of the analysis, it is observed that the law is barely complied with, speaking through erasures and without delving into important points about racial discussions. It is concluded that changes are necessary for compliance with the law to produce positive effects on the constitution of mathematical identities of black subjects.
VEINTE AÑOS DE LA LEY 10.639: ¿Cómo es efectiva esta ley en una colección de libros de texto de matemáticas?
VINTE ANOS DA LEI 10.639: Como essa lei se efetiva nas coleções de livros didáticos de matemática?
Keywords: ethnic-racial relations; law 10.639/2003; mathematics textbooks